2020
DOI: 10.1038/s41467-020-18134-z
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of a bacterial stress response is a generalizable predictor for fitness and antibiotic sensitivity

Abstract: Current approaches explore bacterial genes that change transcriptionally upon stress exposure as diagnostics to predict antibiotic sensitivity. However, transcriptional changes are often specific to a species or antibiotic, limiting implementation to known settings only. While a generalizable approach, predicting bacterial fitness independent of strain, species or type of stress, would eliminate such limitations, it is unclear whether a stress-response can be universally captured. By generating a multi-stress … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…The increasingly ubiquitous RNA-seq data have been used to predict the transcriptional regulatory networks in S. aureus , where antibodies for most regulators are not readily available [ 36 ]. These data have also been used to predict fitness and sensitivities to different antibiotics in different pathogens [ 37 ]. In parallel to RNA-seq–based approaches, metabolic modeling has also come to the forefront of the effort to understand resistance mechanisms.…”
Section: Results and Validationmentioning
confidence: 99%
“…The increasingly ubiquitous RNA-seq data have been used to predict the transcriptional regulatory networks in S. aureus , where antibodies for most regulators are not readily available [ 36 ]. These data have also been used to predict fitness and sensitivities to different antibiotics in different pathogens [ 37 ]. In parallel to RNA-seq–based approaches, metabolic modeling has also come to the forefront of the effort to understand resistance mechanisms.…”
Section: Results and Validationmentioning
confidence: 99%
“…The long-term antibiotic therapy may alter not only the abundance of some species, but also the bacterial fitness, defined as the ability of bacteria to adjust their metabolism to adequately suit environmental conditions, thereby being able to survive and grow; this concept is considered a major physiological determinant [108][109][110]. Under certain conditions, including antibiotic therapy, bacteria with low fitness could be favorized, having significantly high and fluctuating gene expression changes that exceed bacteria with high level fitness [111][112][113]. Regarding possible modifications of gene expression of the gut bacteria in patients with CRC under antibiotic therapy, further research is needed to demonstrate these potential changes and also their impact on microbial virulence, antibiotic resistance and overall outcome of the patients.…”
Section: Impact Of Long-term Tetracyclines On Gut Microbiome In Metastatic Crc Patientsmentioning
confidence: 99%
“…In a seminal study, Zhu et al showed that bacteria of different species respond in a similar fashion to antibiotic stressors [ 22 ]. Although bacterial stress responses include many different genetic pathways that depend on the type of stressor and the bacterial species involved, a generic stress response could nonetheless be observed when considering the whole system dynamics (i.e., when observing the whole gene transcription activity as measured in terms of differential mRNA expression in time).…”
Section: Disorder As a Common Response Of Organisms To High Levels Of Stressmentioning
confidence: 99%
“…Such ‘disorder’ can be expressed in terms of a statistical quantity called permutation entropy, which is a measure of the amount of randomness that can be observed in the covariance patterns the describe the relationships between the various components of a system ( Box 1 ). Zhu et al noted that the observed rise in disorder scores resulted from large-amplitude changes that were produced by independently responding genes, and that this independence may result from of a loss of regulatory connections that normally synchronize gene activity to produce order ( Figure 2 ) [ 22 ]. As it turns out, permutation entropy levels in the timeseries of bacterial gene expression predict bacterial fitness (defined as the growth and survival rates of bacteria).…”
Section: Disorder As a Common Response Of Organisms To High Levels Of Stressmentioning
confidence: 99%